Population parameters and exploitation rate of Sarotherodon melanotheron melanotheron rüppell, 1852 (Cichlidae) in Lake Toho, Benin. - LEDEROUN, DJIMAN; CHIKOU, ANTOINE; Vreven, Emmanuel; Snoeks, Jos; MOREAU, Jacques; Vandewalle, Pierre; LALEYE, PHILIPPE A. (My University, 2015)
Aspects of the population dynamics of Sarotherodon melanotheron melanotheron, which is a commercially important fish species in Lake Toho, were described based on 1558 specimens collected monthly between January and December 2012 from artisanal captures. The size at first maturity was estimated at 6.9 cm for males and 7.7 cm for females. The asymptotic length obtained by analyzing frequency data with FiSATII software (FAO-ICLARM) has been estimated at 21.5 cm. Further, the von Bertalanffy growth coefficient was 0.58 year-1 and the overall growth performance index was 2.43. The estimates of the total, natural and fishing mortalities were 1.95, 1.37 and 0.58 year -1 respectively. The current exploitation rate was 0.30 and as such, remains below the maximum exploitation rate which was 0.55 according to the selection ogive procedure. However, this value is superior to the exploitation rate at 50% of its unexploited biomass (E0.5 = 0.27). Therefore, a reduction of the current exploitation rate is needed by, at least, 10% to maintain a sufficient biomass. The size at first capture was estimated at 6.7 cm which is lower than the size at first maturity for both sexes, but especially for females. These parameters clearly reflect a current trend of overexploitation.
Keywords: Demographic parameters; Lake Toho; Mono basin; Sarotherodon melanotheron melanotheron; West Africa.